An effectiveness of communication in project undertaking: problems and constraints - Mohd. Yusuf, Aminah; Abd. Majid, Muhd. Zaimi; Zakaria, Rozana (Universiti Teknologi Malaysia, 2001)
Effective communication is vital in the project undertaking. This due to the fact that construction project involve many parties and stages. Due to this complicated nature parties in the project should committed to ensure the completion of project within time, cost and quality stipulated. Despite realizing the importance of this integrated effort in project undertaking, time and cost over-run had long been common phenomena in construction industry. The phenomenon has become synonym with the industry. The problems are commonly related to ineffectiveness of communication in project. This research aims at investigating communication's problems in project undertaking and further attempt to identify constraints to effective communication in project. The literature review has successfully explored some important issues related to communication which provides some guide to the questionnaires preparation. Surveys performed on selected respondents. The information gathered been analyzed to derive some findings. The research found that communication involves a transmission of information from one party to another in the essence that appropriate action can be undertaken. What are communications problems in project? Poor coordination and documentation have been major contributors to the poor communication. Coordination is frequently related to inability of project coordinator to coordinate the team's member. Poor documentation has been identified as a result of tendency to cut cost amongst project member. Additionally, the selection of appropriate medium of communication become of the critical communication success factor. Meeting has been one of efficient method for the selected case study. The research also realized that organization’s internal crisis could pose constraints to the communication as well as inadequate understanding on goal of the job performed. It's getting worse with the attitude of project's member and failed to share the foal of the project.